Curculigoside attenuates oxidative stress and osteoclastogenesis via modulating Nrf2/NF-κB signaling pathway in RAW264.7 cells. (15th July 2021) - Liu, Mengqin; Liu, Sha; Zhang, Qi; Fang, Yingqi; Yu, Yanwei; Zhu, Lulin; Liu, Yuling; Gong, Wan; Zhao, Luying; Qin, Luping; Zhang, Qiaoyan
Abstract: Ethnopharmacological relevance: Curculigo orchioides Gaertn is used for the treatment of impotence, atrophic debility of bones (osteoporosis), limb limpness, and arthritis of the lumbar and knee joints in traditional Chinese medicine and Ayurvedic medical system. Curculigoside (Cur) from Curculigo orchioides Gaertn has been shown to have regulatory effects on bone metabolism via anti-oxidative activities in rats and osteoblasts. However, little is known about the molecular pharmacological activity of Cur in osteoclastic bone resorption. Aim: The aim of this work is to investigate the inhibitory effect of Cur against osteoclasts (OCs) under the oxidative stress status, and explore the possible underlying mechanism. Materials and methods: OCs were induced from RAW264.7 cells using RANKL and H2 O2 . The number of OCs was measured by tartrate-resistant acid phosphatase (TRAP) staining. F-Actin and nuclear translocation of P65 and Nrf2 were stained with immunofluorescence assay and observed under a laser confocal microscope. The biochemical parameters of OCs were detected with an ELISA kit. The expression of Nrf2 and NF-κB pathway-related proteins was analyzed by Western Blot. Results: Cur inhibited the TRAP activity, release of degrading products from bone slices and the expression of NFATc1, c-Fos, Cathepsin K (Ctsk) and matrix metallopeptidase 9 (MMP9) of OCs induced with RANKL and H2 O2 . In addition, Cur suppressed the ROS level and NADPH oxidase 1(NOX1) and NADPH oxidase 4 (NOX4) activities of OCS. More importantly, Cur enhanced the expression and nucleus translocation of Nrf2 and activities of its regulatory cytoprotective enzymes, and reduced the NF-κB expression and phosphorylation and nucleus translocation of p65 in OCs. Furthermore, the Nrf2 inhibitor ML385 and NF-κB inhibitor Bay11-7082 counteracted the effect of Cur in OCs. Conclusion: Cur mitigated oxidative stress and osteoclastogenesis by activating Nrf2 and inhibiting the NF-κB pathway, suggesting that Cur may prove to be a promising candidate for the treatment of osteoporosis. Our findings may also help partially explain the rationale behind the traditional use of Curculigo orchioides Gaertn. Graphical abstract: Image 1 Highlights: Curculigoside attenuates the oxidative stress in osteoclast induced from RAW264.7 cells. Curculigoside inhibits bone resorption of osteoclast induced from RAW264.7 cells. Curculigoside involves into the regulation of NF-κB and Nrf2 pathway in osteoclast.